Strategi Perencanaan Investasi Pariwisata di DPMPTSP Kota Prabumulih - Riko Prayudi Septa; Maulana Maulana; Alamsyah Alamsyah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Riko Prayudi. This study aims to analyze the DPMPTSP Strategy Formulation in Planning Tourism Investments in Prabumulih City. The study used qualitative methods with data collection, namely observation, interviews and documentation. The results show that from the aspect of vision and mission, it can be guaranteed that the Office of Investment and One Stop Integrated Services (DPMPTSP) of Prabumulih city has tried to realize the vision that has been set by carrying out several missions that have been determined. Identification of External Opportunities and Threats of an Organization From the Aspects of Identification and External Threats An organization can open that there are still many opportunities for Prabumulih City to develop but also many future threats if the Prabumulih City DPMPTSP does not improve and does not adapt to the times. From the aspect of Awareness of the Strengths of Internal Strengths and Weaknesses, it can be said that there is tourism potential and hotels that can support investment into Prabumulih city, while the weakness is in the minimal natural tourism potential and the problem of weak human resources. From the aspect of Long-Term Determination that the long-term goal of what DPMPTSP wants to achieve in planning tourism investment in Prabumulih City is to make Prabumulih city a developed city and then increase the economic growth of the Prabumulih City community. From the aspect of Searching for Alternative Strategies, it can be said that the strategic plan has been implemented properly through the vision, mission and goals that have been set so that it is easier to realize what is the hope of making Prabumih City Prima.